Identification of Contact Stiffness between Brake Disc and Brake Pads Using Modal Frequency Analysis - Haizhou Ding; Qiang Zhu; Hongming Lyu (Journal of Engineering and Technological Sciences, 2020)
The contact stiffness between brake disc and brake pads is a vital parameter that affects brake NVH performance through increasing the system stiffness and modal frequencies. In order to establish accurate contact behavior between brake parts for further research on precise modeling of disc brakes, a method of identifying the normal contact stiffness of a floating caliper disc brake was developed in this study based on modal frequency testing and finite element analysis. The results showed that contact stiffness increases with brake pressure due to compression of the friction material and increases with the disc mode order at lower-order modes but almost stays invariant at higher-order ones due to contact area variation.